Comparison of Premium Reserves with New Jersey Methods and Full Preliminary Term on Endowment Insurance - Filemon Febrian Bintoro; Fauziah Nur Fahirah Sudding (Journal of Actuarial, Finance, and Risk Management, 2022)
Life insurance companies often have difficulty getting fees at the beginning of the insurance year. It’s noted that there are several life insurers who suffer losses caused by the inability to pay compensation to the insured, because the value of the claim insured submit exceeds the cliam estimated by the insurer. Those conditions can be anticipated if the insurance company has reserve funds. This study aims to find the right reserve value for insurance companies that have been adapted to endowment life insurance using the New Jersey and Full Preliminary Term method. Based on the data analysis carried out, it was concluded that the New Jersey reserve value for male from 1st year to 49th year is greater than that for females. Meanwhile, for Full Preliminary Term reserves, the value of male’s reserves from the 1st year to the 49th year is relatively always greater than that of females. This research could be used as a reference for insurance company to consider the better method in calculating premium reserves based on its policyholder profile